United States of America, plaintiff, vs Robert Edward Miles; Louis Ray Beam, Jr.; Richard Girnt Butler; Richard Joseph Scutari; Bruce Carrol Pierce; Andrew Virgil Barnhill; Ardie McBrearty; David Eden Lane; Lambert Miller; Robert Neil Smalley; Ivan Ray Wade; William H. Wade; Richard Wayne Snell; David Michael McGuire; defendants - Miles, Robert E.; Beam, Louis R.; Butler, Richard G.
Photocopied sheets of complete criminal proceedings of CR 87-20008, commonly known as the Fort Smith sedition trial, held in the United States District Court for the Western District of Arkansas, Fort Smith Division, 1987-1988.